2018
DOI: 10.20452/pamw.4317
|View full text |Cite
|
Sign up to set email alerts
|

Unfavorably altered plasma clot properties in women with HERDOO2 above 1 and prediction of recurrent venous thromboembolism

Abstract: Introduction The HERDOO2 rule can help identify patients in whom anticoagulation can be safely discontinued. Unfavorably altered fibrin clot properties predict recurrent venous thromboembolism (VTE). Objectives We aimed to assess a possible association between fibrin clot properties and the HERDOO2 score in women after unprovoked VTE. Patients and methods Eighty women younger than 70 years after a first unprovoked VTE separately and combined with 32 women after hormone‑related VTE were followed for a median of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It is known that the presence of HRG in fibrin clots significantly affects the structure of the clot by causing the formation of thinner fibrils 18 , which results in denser networks that are usually more resistant to lysis 11 . Since fibrin is the main component of all venous thrombi 29,30 , elevated circulating HRG levels likely lead to augmented incorporation of this protein into fibrin networks and the subsequent disturbed degradation of fibrin and possible harmful local actions. Our findings suggest that HRG may contribute to the development of PTS via prothrombotic alterations to fibrin structure and function.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the presence of HRG in fibrin clots significantly affects the structure of the clot by causing the formation of thinner fibrils 18 , which results in denser networks that are usually more resistant to lysis 11 . Since fibrin is the main component of all venous thrombi 29,30 , elevated circulating HRG levels likely lead to augmented incorporation of this protein into fibrin networks and the subsequent disturbed degradation of fibrin and possible harmful local actions. Our findings suggest that HRG may contribute to the development of PTS via prothrombotic alterations to fibrin structure and function.…”
Section: Discussionmentioning
confidence: 99%
“…63 Female patients following unprovoked VTE associated with elevated risk of its recurrence based on a HERDOO2 score (2) have been observed to display impaired fibrinolysis determined 3 months since the index event, and prolonged CLT >99.5 minutes, along with reduced clot density, was associated with high risk of VTE recurrence, thus providing additional arguments to support the view of a predictive value of fibrinolysis measures following VTE. 62,64 Very recently, Medeiros et al have shown that there was a larger proportion of clots made from plasma of patients with unprovoked VTE that were resistant to lysis (43.7%) compared with healthy subjects (0%); however, cell free DNA levels were not associated with impaired fibrinolysis among unprovoked VTE patients who stopped a mean 5-month oral anticoagulation. 65 Cancer patients make up to 20% of all individuals with newly diagnosed VTE.…”
Section: Fibrinolysis Following Vtementioning
confidence: 99%